Rapid Mass Loss in West Antarctica Revealed by Swarm Gravimetry in the Absence of GRACE. Issue 23 (9th December 2021) - Zhang, Chaoyang; Shum, C. K.; Bezděk, Aleš; Bevis, Michael; de Teixeira da Encarnação, João; Tapley, Byron D.; Zhang, Yu; Su, Xiaoli; Shen, Qiang
Abstract: GRACE observations revealed that rapid mass loss in the West Antarctic Ice Sheet (WAIS) abruptly paused in 2015, followed by a much lower rate of mass loss ( 21.3 ± 5.7 $21.3± 5.7$ Gt yr −1 ) until the decommissioning of GRACE in 2017. The critical 1‐year GRACE intermission data gap raises the question of whether the reduced mass loss rate persists. The Swarm gravimetry data, which have a lower resolution, show good agreement with GRACE/GRACE‐FO observations during the overlapping period, i.e., high correlation (0.78) and consistent trend estimates. Swarm data efficiently bridge the GRACE/GRACE‐FO data gap and reveal that WAIS has returned to the rapid mass loss state ( 161.5 ± 48.4 $161.5± 48.4$ Gt yr −1 ) that prevailed prior to 2015 during the GRACE intermission data gap. The changes in precipitation patterns, driven by the climate cycles, further explain and confirm the dramatic shifts in the WAIS mass loss regime implied by the Swarm observations. Plain Language Summary: The West Antarctic Ice Sheet (WAIS) rests largely below sea level, and so is particularly vulnerable to anthropogenic climate change. The space gravimetry mission GRACE revealed that WAIS mass loss had accelerated until rapid mass loss abruptly paused in 2015. The much‐reduced rates of ice mass loss prevailed until the middle of 2017, when the GRACE mission terminated, leaving a 1‐year data gap before GRACE‐FO resumed the measurement time series. We find the lower resolution Swarm gravimetry data have good consistency with GRACE and can be used to span this data gap. The Swarm observations reveal that WAIS has returned to the rapid mass loss state (observed prior to 2015) during the 2017–2018 data gap. Atmosphere pressure data suggest that a persistent low air pressure near Antarctic Pacific sector during 2015–2017, led to increased precipitation over West Antarctica. It then sharply transitioned into a high‐pressure state during 2017–2019, which prevented the inflow of warm and moist air to West Antarctica. The resulting changes in precipitation and extreme El Niño to La Niña transition can jointly explain the major changes in the mass loss regime observed by Swarm in West Antarctica. Key Points: Swarm mass anomalies estimates, though noisier, are consistent with GRACE estimates (correlation 0.78) in West Antarctic Ice Sheet (WAIS) Swarm reveals that WAIS returned to the rapid mass loss state (161.5 ± 48.4 Gt yr −1 ) prevailed prior to 2015 in the GRACE intermission gap